2003
DOI: 10.1046/j.1439-0272.2003.00534.x
|View full text |Cite
|
Sign up to set email alerts
|

Tissue kallikrein and bradykinin B2receptors in the reproductive tract of the male rat

Abstract: The setting of a local tissue kallikrein kinin system (tKKS) within the reproductive organs of the male rat was investigated by analysing bradykinin subtype 2 receptor (B2R) gene expression and cellular distribution of B2R protein and the kinin-liberating protease tissue kallikrein (tK). Reverse transcription-polymerase chain reaction showed B2R expression in testis, epididymis and prostate from prepubertal and sexually mature rats. In mature testis, in situ hybridization and immunohistochemistry localized B2R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Miska et al [191] showed that porcine pancreatic kallikrein, which is taken orally, is absorbed in unaltered form by the intestine. In the light of the recent data by Monsees et al [178-180] obtained in the rat, the kallikrein-kinin system in the male reproductive tract seems to play a role in the regulation of Sertoli cell function, the local regulation of spermatogenesis or in the function of the seminiferous tubules.…”
Section: In Vitro Treatment Of Spermatozoamentioning
confidence: 98%
See 1 more Smart Citation
“…Miska et al [191] showed that porcine pancreatic kallikrein, which is taken orally, is absorbed in unaltered form by the intestine. In the light of the recent data by Monsees et al [178-180] obtained in the rat, the kallikrein-kinin system in the male reproductive tract seems to play a role in the regulation of Sertoli cell function, the local regulation of spermatogenesis or in the function of the seminiferous tubules.…”
Section: In Vitro Treatment Of Spermatozoamentioning
confidence: 98%
“…Despite all components of the kallikrein-kinin system are present in the male and female genital tract [177,178] and the localization of the bradykinin B 2 -receptor in rat testis [179,180], the function of the kallikrein-kinin system for male reproductive function is still unclear. The prostate-specific human glandular kallikrein, which is about 500-times less effective than tissue kallikrein, is present in human seminal plasma [181].…”
Section: In Vitro Treatment Of Spermatozoamentioning
confidence: 99%
“…No definite evidence is yet available on whether vas deferens epithelial cells synthesize and secrete TGFB, but immunohistochemical data are available to support that epididymal epithelia do [28]. Moreover, local activation of TGFB is a key regulatory mechanism for signaling [41,42] and, interestingly, epididymal epithelia express proteases that activate TGFB [43,44]. The luminal environment of the male excurrent duct also presents segmental pH variability, which, in segments such as the cauda epididymis, reaches fairly acidic levels.…”
Section: Pierucci-alves Et Almentioning
confidence: 99%
“…A role for kinins in the genitourinary system has been speculated upon due to the presence of prostate-specific antigen and other kallikreins (Fichtner et al, 1996;Monsees et al, 2003). Differences in the amounts of kallikreins in the prostate are being proposed as a marker to distinguish between normal, cancerous and benign prostatic hyperplasia (Scorilas et al, 2003).…”
Section: Discussionmentioning
confidence: 99%